Perbandingan Karakteristik Plastik Biodegradable dari Biji Durian menggunakan Filler Kalsium Silikat dan Kalsium Karbonat - S. Sigit Udjiana; Sigit Hadiantoro; Noor Isnaini Azkiya (Politeknik Negeri Malang, 2021)
In this study, durian seeds were used as a source of starch in making biodegradable plastics. This study aims to determine the effect of the type and amount of filler on biodegradable properties, mechanical properties, and water absorption properties of biodegradable plastics based on durian fruit starch. The plasticizer used in this study was sorbitol 40%, while the filler used was Calcium silicate (Ca2SiO4) and Calcium carbonate (CaCO3) with variable concentrations of 2%, 4%, 6%, and 8%. From the research results, the% yield of durian seed starch was 34.57%. The results of the best biodegradable plastic with the characteristics of transparent, no bubbles, flexible and smooth surface were obtained with the addition of 4% calcium carbonate filler variables. The bio-degradation test results closest to the ASTM D6400 standard were obtained in the 2% calcium carbonate variable. In the water absorption test, the best results were achieved at the 8% calcium silicate variable. The best tensile test results were obtained in the 6% calcium silicate variable.